Immunomodulatory Activities of Atractylodes lancea (Thunb.) DC - Kulma, Inthuon; Panrit, Luxsana; Plengsuriyakarn , Tullayakorn; Chaijaroenkul , Wanna; Warathumpitak , Siriprapa; Na-Bangchang , Kesara (Current Practice in Medical Science Vol. 7, 2022)
In vitro and In vivo research have shown that Atractylodes lancea (Thunb) DC. (AL) and its bioactive components -eudesmol and atractylodin could be used to treat cholangiocarcinoma. The study aimed to evaluate the immunomodulatory activity of AL in human subjects. The modulatory effects of AL and b-eudesmol and atractylodin on TNF\(α\) and IL6 expression in PBMCs were measured using real-time PCR. Blood samples were taken from 48 healthy subjects after they were given a single or numerous doses of the standardised AL extract capsule formulation or a placebo. Serum cytokine profiles, lymphocyte subpopulations (B lymphocytes, CD8+ cytotoxic T lymphocytes, CD4+ T-helper lymphocytes, and NK cells), and cytotoxic activity of PBMCs against the cholangiocarcinoma cell line CL-6 were evaluated using cytometric bead array (CBA) with flow cytometry analysis. AL extract at almost all concentrations significantly inhibited both TNF\(α\) and IL6 expression in Con A-mediated inflammation in PBMCs. Only IL6 expression was significantly reduced by \(β\)-Eudesmol at all doses. At the lowest dose, atractylodin considerably decreased the expression of both cytokines, whereas at the highest concentration, only IL6 expression was significantly inhibited. The administration of AL at a single oral dose of 1,000 mg appeared to decrease IFNg and IL10 and increase B cells, while significantly increasing NK and CD4+ and CD8+ cells. At 24 hours after dosage, there was a trend of increasing cytotoxic activity of PBMCs (relative to placebo). At 24 hours after dosage, AL at successive doses of 1,000 mg for 21 days tended to reduce the production of all cytokines while significantly suppressing IL17A production. By 24 hours, there was a trend of increased cytotoxic activity in PBMCs, but this trend stopped at 48 hours. The findings support AL's immunomodulatory properties in humans. This activity, together with AL's direct effect in triggering apoptosis in cholangiocarcinoma cells, implies that it could have a role in CCA regulation. Trial Registration: Retrospectively registered on 17 October 2020 [Thai Clinical Trials Registry (TCTR: www.clinical trials.in.th) Number TCTR20201020001]